Effectiveness of Using Demonstration Learning Method for Grade X Students in Archiving Subject at SMK Nurul Qalam Makassar - Amelia Ramadhani; Nasaruddin Hasyim; Jamaluddin (ASHA Publishing, 2024)
Effectiveness is a condition that shows the extent to which something that is planned can be achieved and has an influence on something that is planned. This study aims to determine the effectiveness of the use of demonstration learning methods for class X in the subject of archiving at SMK Nurul Qalam Makassar. This study is a qualitative descriptive study. The study determined 5 informants, namely: Archiving subject teachers, and 4 class X students of the OTKP Department with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the effectiveness of the use of demonstration learning methods for class X in the subject of archiving at SMK Nurul Qalam Makassar which is carried out by subject teachers is quite effective. Judging from the indicators of the use of the demonstration method in this study, namely the planning stage, the formulation of objectives conveyed by the teacher has been carried out well and clearly to students, although activities such as conducting demonstration trials and outlines of demonstration steps have not been carried out. Furthermore, at the implementation stage, the demonstration method runs smoothly and the activities in the implementation steps are carried out optimally even though the provision of tools and practical materials and the arrangement of student seating are not optimal and need to be considered. Then the stage of ending the demonstration method is carried out well by the teacher by conducting an evaluation at the end of the learning process with the aim of determining the level of student achievement in the learning process.